Direct Acting Antivirals for the Treatment of Chronic Viral Hepatitis. (25th November 2012) - Karayiannis, Peter
Abstract : The development and evaluation of antiviral agents through carefully designed clinical trials over the last 25 years have heralded a new dawn in the treatment of patients chronically infected with the hepatitis B and C viruses, but not so for the D virus (HBV, HCV, and HDV). The introduction of direct acting antivirals (DDAs) for the treatment of HBV carriers has permitted the long-term use of these compounds for the continuous suppression of viral replication, whilst in the case of HCV in combination with the standard of care [SOC, pegylated interferon (PegIFN), and ribavirin] sustained virological responses (SVRs) have been achieved with increasing frequency. Progress in the case of HDV has been slow and lacking in significant breakthroughs.This paper aims to summarise the current state of play in treatment approaches for chonic viral hepatitis patients and future perspectives.